Efektivitas Analgetik Nanopartikel Kitosan-Ekstrak Etanol Daun Pepaya (Carica Papaya L.) Pada Mencit Putih Jantan (Mus Mucculus) - Juliferd Gredi; Wintari Taurina; Mohamad Andrie (JURNAL ILMU KEFARMASIAN INDONESIA, 2017)
Papaya leaves has been shown to have efficacy as an analgesic. Analgesic effect caused by the flavonoids in leaves of papaya. To enhance the analgesic effi cacy papaya into dosage formulatio of nanoparticles. The purpose of this research was to create and characterized nanoparticles from ethanol extract of papaya leaves then tested for effectiveness as an analgesic. This study used polymer chitosan and NaTPP to created nanoparticles through ionic gelation method and analgesic activity tested using writhing test method and statistical tested. Optimal formula of nanoparticles were produced at concentration of 0.2% chitosan, Na-TPP extract 0.1% and 4% with a ratio of 6: 1: 1. The nanoparticles was formed a size of 255.4 nm with polidispers index of 0.7, the zeta potential of + 11,1mV, the adsorption effi ciency by 87% and rounded morphology (spherical). Analgesic effectiveness tested by comparison between the groups ethanol extract of papaya and the groups nanoparticles of chitosan-ethanol extract papaya statistically using the T-test Independent. The results of this research indicate that there are statistically signifi cant differences (p <0.05). This results shows that the preparation nanoparticles of chitosan-ethanol extract papaya is more effective as an analgesic than the ethanol extract of papaya leaves.